Evidence for motor imagery in the management of vestibular disorders does not support recent guidelines: A systematic search and review - Dimitri Fabre-Adinolfi; Florian Naye; Thomas Rulleau (PLoS ONE, 2026)
Context Vestibular disorders significantly impact people’s quality of life, affecting functions such as balance and walking. Current treatments involve pharmacological and non-pharmacological approaches, with vestibular rehabilitation proving effective in helping to compensate for deficits. Although traditional techniques address various aspects of the vestibular system, many fundamental studies suggest motor imagery could reduce vestibular impairment. Despite the paucity of research on motor imagery for vestibular disorder rehabilitation, recent expert recommendations suggest it could enhance functional recovery. This review questions the evidence in the literature on the clinical value benefits of motor imagery as part of vestibular rehabilitation. The aims of this study were 1. to identify motor imagery interventions used in the literature, 2. to critically appraise them, and 3. to report their impact on clinical outcomes. Methods We conducted a systematic search using the PubMed, Cochrane Library, Web Of Science, CINAHL and Scopus databases. The review was registered on PROSPERO and is reported according to the PRISMA guidelines. PICO criteria were adults undergoing a motor imagery intervention as part of vestibular rehabilitation, studies with or without comparators, and the use of clinical outcome measures. A critical grid was completed, and a risk of bias assessment was performed. Results Despite identifying 2404 (after duplicate removal) concerning motor imagery and vestibular rehabilitation, only two articles met our inclusion criteria. Our findings suggest a clinical benefit of integrating motor imagery into vestibular rehabilitation. However, the limited evidence and methodological shortcomings warrant caution, including small sample size, absence of imagery quality assessment, and poor generalizability. Conclusion Future research should address the identified limitations, including the need to study a broader range of vestibular pathologies, use comprehensive assessments, and evaluate long-term effects. This would contribute to a more thorough understanding of motor imagery as part of vestibular rehabilitation. Trial registration PROSPERO CRD42023444673